Penerapan Digital Marketing (Aplikasi Jiva) Sebagai Upaya Peningkatan Pendapatan di LMDH KPH Mojokerto - Rista Nur Rahmaniah; Ida Syamsu Roidah (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2023)
The provision of Digital Marketing socialization aims to utilize the marketing strategy of corn commodities in the Forest Village Community Institution (LMDH) Watu Blorok, Jolotundo Village, Jetis District, Mojokerto Regency. To maximize the potential of online marketing, many organizations use various digital tools and platforms. An application that has received attention in digital marketing is the Jiva application. Gives a clear and detailed overview of digital marketing, and analyzes its potential for effective implementation. Digital marketing includes a set of strategies and techniques used to promote products, services through online channels. Jiva app, is specially developed to offer various features and functions that can improve the efficiency and effectiveness of digital marketing. Finally, this paper highlights the importance of digital marketing in the context of the digital age and illustrates the potential of the Jiva app in implementing effective strategies. By leveraging its advanced features, the Jiva app helps organizations expand their reach, improve interactions with customers, and achieve marketing goals. The benefits offered by the Jiva app make it a valuable tool in digital marketing efforts